Implementing graph representation model for parallel and distributed systems using Erlang - Petrov, Iurii (Computer Science, 2016)
This paper describes a new model of graph representation using the Erlang actor model. Benefits of using lightweight processes instead of traditional passive data structures are given. Examples of using this model are shown. The experimental part gives two examples of using early implementations of the offered model. As a conclusion, an analysis of applicability for tasks from different branches of science is given.